1991
DOI: 10.1007/bf00052138
|View full text |Cite
|
Sign up to set email alerts
|

Dietary risk factors in intestinal and diffuse types of stomach cancer: a multicenter case-control study in Poland

Abstract: A hospital-based, multicenter, case-control study has been performed in Poland covering 741 incident stomach-cancer cases (520 males and 221 females) and the same number of controls. All stomach-cancer diagnoses were evaluated for histologic type according to the Lauren criteria. Fifty-one percent were of the intestinal type, 35 percent of the diffuse type, and 8.5 percent of the mixed type. The frequency of consumption of individual food items and several food groups was analyzed and the association of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
2
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 18 publications
3
43
2
2
Order By: Relevance
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
“…19,[35][36][37][38] An earlier pathology investigation in Ardabil had found that 49.5% of GC were diagnosed in cardia. 39 We also found the previously reported association between GC and a positive family history [15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Among case-control studies, 5 studies [22][23][24][25][26] have found a 2-to 3-fold statistically significant increase in stomach cancer risk associated with high consumption of processed meat, 6 studies 27-32 have observed a 30-70% increased risk but the results were not statistically significant, and 2 studies did not support an association. 33,34 In some case-control studies, positive associations were found for specific processed meat items, including bacon, 35,36 sausage 35,37,38 or ham. 35,39 The evidence from prospective cohort studies is less supportive of an association between processed meat consumption and risk of stomach cancer.…”
Section: Discussionmentioning
confidence: 99%